Social Activation of the Khambu Ethnic in Nepal's Indigenous Movement - Rai , Ram Kumar (HISAN: Journal of History Association of Nepal, 2024)
The paper analyses the social and political movement of Khambu communities of Nepal, focusing on historical political and cultural perspectives. It brings into light the essential causes and consequences of the rise and settlement of all ethnic movements in Nepal. The paper argues that the ethnic group of Eastern Nepal known as the Khambu, due to historical changes, has transitioned from a revivalist movement to a national autonomy movement. Understanding the Khambu people's position concerning other ethnic groups in Nepal and their effects outside of the country will be beneficial. The paper is presented inductively and the choice of methodology is qualitative.